Effect of Brain-Based Learning on Students’ Conceptual Understanding of Plant Tissues - Zulfa Safinatun Naja Medina; Jujun Ratnasari; Setiono (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Understanding plant tissue structure is a fundamental yet challenging topic in biology learning due to its abstract and microscopic characteristics. Innovative and contextual learning models are needed to improve students’ cognitive learning outcomes. This study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The participants were 44 eleventh-grade students from a public senior high school in Sukabumi, divided into an experimental group taught using the Brain-Based Learning (BBL) model with local plants and a control group taught using the Discovery Learning model. Data were collected through pre-tests and post-tests and analyzed using N-Gain analysis and an independent sample t-test. The results showed that the experimental group achieved a higher average N-Gain score (0.6748, medium-high category) compared to the control group (0.3790, medium category). The independent sample t-test indicated a statistically significant difference between the two groups (p < 0.05), demonstrating the effectiveness of the BBL model in improving students’ cognitive learning outcomes. The integration of local plants as contextual learning media within the BBL framework supports students’ conceptual understanding based on Bloom’s Taxonomy, particularly in interpreting, summarizing, and explaining plant tissue concepts. The Brain-Based Learning model is an effective alternative approach for enhancing cognitive learning outcomes in biology, especially for complex conceptual materials such as plant tissue structure.